Implementing a WTO Agreement on Trade Facilitation : What Makes Sense? - Finger, J. Michael (World Bank, Washington, DC, 2012)
Contrary to the prevailing view that the Doha negotiations have achieved little, the authors find that on trade facilitation much progress has been made. This is particularly true in regard to action by development banks and bilateral development agencies to meet client demand for assistance in reform. Active private sector participation has been an important factor driving change. Many agencies have been involved in this work. The authors find that their roles have been consistent with their comparative advantages. As to how the international community can best support continued progress, the authors conclude in favor of a cautious approach to the imposition of new WTO obligations in the area of trade facilitation. On the whole, this is the approach the WTO has taken, for example, by limiting its negotiations on trade facilitation to several specific provisions of the GATT. The WTO can continue to function as a catalyst for reform. It is perhaps uniquely placed to relate the trade facilitation agenda to the overall trade agenda. On design and construction of the relevant infrastructures and capacities to spur development, the development institutions, including bilateral agencies, should continue to lead. The authors find little evidence to support the need for a comprehensive new "platform" or mechanism to channel trade-related aid as part of implementation of any new agreement at the WTO on trade facilitation. They recommend, however, that an innovative approach to using the well established, but under utilized Trade Policy Review Mechanism be considered to increase transparency on where new aid is going over time and to expand understanding of where and how country-based progress has been achieved.